Preparation of dynamic assessment instruments to improve the understanding of student concepts about disease - Afrizal Mahmud; Murni Ramli; Yudi Rinanto (Universitas Muhammadiyah Malang, 2025)
Students often experience difficulties in understanding virus concepts as disease pathogens in biology, making Dynamic Assessment (DA) a promising approach to support conceptual learning through prompts. The purpose of this study was to develop a DA test to improve students' conceptual understanding in 10th grade students about the virus as a disease pathogen and the validity of the instrument. This research is using descriptive qualitative method to explain the steps of arranging DA instrument test. The first was analyzing the literature review to determine the DA format to improve students' cognitive aspects from various international journal databases. The second step was preparing the DA draft. The third step was validating the instrument by experts and assessors. The fourth step was to perform a small-scale test of the instrument. The final step was analyzing the item validity and reliability by using Rasch model and Winstep application. The result shows that the raw variance explained by measures validity is a good criterion by 53.6%. The 1st unexplained variance value of 1.6 resulted in eigenvalue indicating adequate item and observed value of 15% indicating item fit. The result of item reliability is a good criterion by 0.88, while the result of person reliability is an average criterion by 0.70. It can be concluded that the DA test instrument is valid and proper to use.